Science in progress : the society of the SIGMA XI devoted to the promotion of research in science : national lectureships 1937 and 1938 (New Haven : Yale University Press, 1939)
Vols. for <1964-> contain national lectureships of the Society of Sigma Xi and the Scientific Research Society of America.
Also issued online.
SERBIB/SERLOC merged record
Keywords: Science -- Periodicals; Research -- Periodicals; Research -- Periodicals; Science -- Periodicals; Sciences -- Collections; Recherche -- Collections